Curriculum Analysis using Harden’s 10 questions framework: Case study Faculty of Medicine and Health Sciences, University of El Imam EL Mahadi (2018) - Hamed Azoz, Mohammed Eltoum; Ali, Moataz Alhasan; Fadl ella, Nour eldin Eltahir; Baloul, Sakina Salih Amed (مجلة الجزيرة للعلوم الصحية; مجلد 14 عدد 2 (2018), 2018)
Introduction: Curriculum analysis is defined as unpacking a curriculum into its component parts , evaluating how the parts fit together, checking underlying beliefs and assumptions and seeking justification for curriculum choices and assumptions . Methods: This is a qualitative descriptive study analyzing the undergraduate curriculum of Faculty of Medicine and Health Sciences, University of El Imam El Mahdi by adopting Harden’s 10 Questions of curriculum development framework approach. Answering Harden’s questions reflects the fundamental curricular components and how the different aspects of a curriculum framework fit together. Results: The analysis of the curriculum of Faculty of Medicine and Health Sciences, University of El Imam El Mahdi  reveals a curriculum with interactive components. Clear structured objectives and goals reflect the faculty’s vision. The approach for needs assessment is based on a scientific ground, and the curriculum integrated contents have been set to meet national and international requirements. Adopting SPICES strategies helps the faculty and students achieve the objectives of the curriculum. Different motivated instructional methods are adopted compatible  with the program objectives and outcomes. A wide range of assessment methods has been adopted correctly and reliably, and in alignment with the intended outcomes to assess the learning outcomes of the curriculum. The Faculty of Medicine and Health Sciences, University of El Imam El Mahdi  has a favorable  educational environment for operation of its curriculum and it has also a well-defined policy for curriculum management, monitoring and evaluation. Conclusion: Harden’s 10 questions are satisfactorily addressed by the multi-discipline and well developed, well-structured, and integrated curriculum of the Faculty of Medicine and Health Sciences, University of El Imam El Mahdi. The curriculum supports the mission and objectives of the faculty.